WNT Stimulation Dissociates a Frizzled 4 Inactive-State Complex with Gα12/13 - Arthofer, Elisa; Hot, Belma; Petersen, Julian; Strakova, Katerina; Jäger, Stefan; Grundmann, Manuel; Kostenis, Evi; Gutkind, J Silvio; Schulte, Gunnar (Molecular pharmacology, 2016)
Frizzleds (FZDs) are unconventional G protein-coupled receptors that belong to the class Frizzled. They are bound and activated by the Wingless/Int-1 lipoglycoprotein (WNT) family of secreted lipoglycoproteins. To date, mechanisms of signal initiation and FZD-G protein coupling remain poorly understood. Previously, we showed that FZD6 assembles with Gαi1/Gαq (but not with Gαs, Gαo and Ga12/13), and that these inactive-state complexes are dissociated by WNTs and regulated by the phosphoprotein Dishevelled (DVL). Here, we investigated the inactive-state assembly of heterotrimeric G proteins with FZD4, a receptor important in retinal vascular development and frequently mutated in Norrie disease or familial exudative vitreoretinopathy. Live-cell imaging experiments using fluorescence recovery after photobleaching show that human FZD4 assembles-in a DVL-independent manner-with Gα12/13 but not representatives of other heterotrimeric G protein subfamilies, such as Gαi1, Gαo, Gαs, and Gαq The FZD4-G protein complex dissociates upon stimulation with WNT-3A, WNT-5A, WNT-7A, and WNT-10B. In addition, WNT-induced dynamic mass redistribution changes in untransfected and, even more so, in FZD4 green fluorescent protein-transfected cells depend on Gα12/13 Furthermore, expression of FZD4 and Gα12 or Gα13 in human embryonic kidney 293 cells induces WNT-dependent membrane recruitment of p115-RHOGEF (RHO guanine nucleotide exchange factor, molecular weight 115 kDa), a direct target of Gα12/13 signaling, underlining the functionality of an FZD4-Gα12/13-RHO signaling axis. In summary, Gα12/13-mediated WNT/FZD4 signaling through p115-RHOGEF offers an intriguing and previously unappreciated mechanistic link of FZD4 signaling to cytoskeletal rearrangements and RHO signaling with implications for the regulation of angiogenesis during embryonic and tumor development.
Keywords: signální transdukce; Signal Transduction; proteiny vázající GTP - alfa-podjednotky G12-G13; Humans; zelené fluorescenční proteiny; proteiny Wnt; Protein Binding; Green Fluorescent Proteins; Fluorescence Recovery After Photobleaching; Wnt Proteins; lidé; proteinové domény; HEK293 Cells; Rho Guanine Nucleotide Exchange Factors; GTP-Binding Protein alpha Subunits, G12-G13; rezonanční přenos fluorescenční energie; faktory zaměňující Rho guanin nukleotidy; Dishevelled Proteins; protein dishevelled; frizzled receptory; HEK293 buňky; vazba proteinů; Protein Domains; FRAP; Fluorescence Resonance Energy Transfer; Frizzled Receptors